Diagnostic and Treatment Challenges of Emergent COVID-Associated-Mucormycosis: A Case Report and Review of the Literature - Manuela Arbune; Anca-Adriana Arbune; Alexandru Nechifor; Iulia Chiscop; Violeta Sapira (MDPI AG, 2022)
Mucormycosis is a rare fungal infection, with high mortality, commonly associated with diabetes, malignancies, immunosuppressive therapy, and other immunodeficiency conditions. The emergence of mucormycosis cases has been advanced by the COVID-19 pandemic. Clinical presentation is variable, from asymptomatic to persistent fever or localized infections. We present a case of a Romanian old man, without diabetes or other immunodepression, with COVID-19 who developed severe rhino-orbital mucormycosis and bacterial superinfections, with Pseudomonas aeruginosa and Klebsiella pneumoniae. The late diagnostic and antifungal treatment was related to extensive lesions, bone and tissue loss, and required complex reconstruction procedures. We review the relationships between mucormycosis, COVID-19, and bacterial associated infections. The suspicion index of mucormycosis should be increased in medical practice. The diagnostic and treatment of COVID-19-Associated-Mucormycosis is currently challenging, calling for multidisciplinary collaboration.